Pengaruh Moralitas Individu, Keefektifan Pengendalian Internal, Perilaku Tidak Etis Terhadap Kecenderungan Kecurangan - Ni Putu Setia Asih; Ni Putu Ayu Kusumawati; Ni Putu Trisna Windika Pratiwi (Hita Akuntansi dan Keuangan, 2022)
This paper is made to describe the influence that is formed between individual morality, effectiveness and internal control, and unethical behavior on the tendency of fraudulent acts. A total of 27 LPDs were used as the population and processed using linear regression analysis technique. From the results of the study it was found that fraud will tend to be high in an institution if its employees commit a lot of deviant actions (unethical behavior). However, the level of fraud can be avoided if employee morale and internal control are improved.